Protection of Civilian Victims of Armed Conflict Based on International Law (Case Study of the Israeli and Palestinian Conflict) - Syailendra Putra, Moody Rizqy; Zimah, Amelia Abdullah; Febriany, Febriany; Rusli, Vennia Neshya (CV. Rayyan Dwi Bharata, 2024)
International armed conflict is defined as a conflict between two or more states or between one state and another party that does not yet have state status. In the world of international law, the Geneva Conventions have been considered the right decision because the results of the convention have been agreed and signed by countries that have been recognized by the United Nations. The essence of the convention is an agreement that protects the safety of military members wounded during the war. In the application of the results of the Geneva Conventions and international human rights law is still not fully applicable. An alliance of countries that gives full support to the Israeli-Palestinian war causes legal defects. The conflict between the two countries has been going on since the early 20th century until now. The Israeli-Palestinian armed conflict is slowly attacking civilians as well. This research is a normative research, which is used to see problems related to armed conflict through legal studies. When viewed from the point of view of the basic state and the principles of the International Law of War, the Israeli-Palestinian war does not follow the existing rules. Several international rules already exist to deal with similar cases, which provide rules and protection. The United Nations here serves to maintain world peace from conflicts between countries.